Precipitation anaIysis in Villa Mercedes (San Luis) 1899/00-1984/85 (Semiárida, 2020)
This paper presents the results of an analysis of rainfall regime in Villa Mercedes (San Luis) from 1899/00 to 1984/85. The rainfall regime in the area is typically mensoonic, 78% of precipitation falling in spring-summer. According to PROHASKA classification the type is Normal dry. More than 50% of the years studied have received between 50 and 70 cm. per year. The highest variability (variance ratio) has been observed during autumn-winter months, 95% confidence intervals for different month rainfall show the validity of monthly averages. The annual rainfall maximum value is 3,57 times greater than the minimum one. Both annual and spring-summer rainfall trends, which have been fortnightly analyzed, are similar r=0,63 and r=0,92 respectively. This show that the annual amount increase is restricted to the wet season. Mean precipitation amount during the autumn-winter period does not reveal the presence of a real trend (r=0.36).